Yhhu3813 is a novel selective inhibitor of c-Met Kinase that inhibits c-Met-dependent neoplastic phenotypes of human cancer cells - He Chang-xi; Ai Jing; Xing Wei-qiang; Chen Yi; Zhang Hao-tian; Huang Min; Hu You-hong; Ding Jian; Geng Mei-yu (Acta Pharmacologica Sinica, 2016)
Chang-xi HE1, #, Jing AI1, #, Wei-qiang XING2, #, Yi CHEN1, Hao-tian ZHANG1, Min HUANG1, You-hong HU2, Jian DING1, Mei-yu GENG1, * 1Division of Anti-tumor Pharmacology, State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai 201203, China; 2State Key Laboratory of Drug Research, Department of Medicinal Chemistry, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai 201203, China Aim: c-Met kinase deregulation is strongly associated with the formation, progression and dissemination of human cancers. In this study we identified Yhhu3813 as a small-molecule inhibitor of c-Met kinase and characterized its antitumor properties both in vitro and in vivo. Methods: The activities of different kinases were measured using ELISA assays and signaling proteins in the cells were detected with Western blotting. Cell proliferation was assessed using SRB or MTT assay in twenty human cell lines and cell cycle distribution was determined with flow cytometry. Transwell-based assay was used to evaluate cell migration and invasion. Cell invasive growth was detected by a morphogenesis assay. c-Met overactivated human NSCLC cell line EBC-1 xenografts were used to evaluate the in vivo anti-tumor efficacy. Results: Yhhu3813 potently inhibited c-Met kinase activity in vitro with an IC50 value of 2.4±0.3 nmol/L, >400-fold higher than that for a panel of 15 different tyrosine kinases, suggesting a high selectivity of Yhhu3813. The compound (20, 100 and 500 nmol/L) dose-dependently inhibited the phosphorylation of c-Met and its key downstream Akt and Erk signal cascades in multiple c-Met aberrant human cancer cell lines, regardless of the mechanistic complexity in c-Met activation across different cellular contexts. In 20 human cancer cell lines harboring different backgrounds of c-Met expression/activation, Yhhu3813 potently inhibited c-Met-driven cell proliferation via arresting cells at G1/S phase. Furthermore, Yhhu3813 substantially impaired c-Met-mediated cell migration, invasion, scattering, and invasive growth. Oral administration of EBC-1 xenograft mice with Yhhu3813 (50 or 100 mg·kg-1·d-1, qd, for 2 weeks) dose-dependently suppressed the tumor growth, which was correlated with a reduction in the intratumoral proliferation index and c-Met signaling. Conclusion: Yhhu3813 is a potent selective inhibitor of c-Met that inhibits c-Met-dependent neoplastic phenotypes of human cancer cells in vitro and in vivo. Keywords: human cancer; anticancer drug; Yhhu3813; c-Met; receptor tyrosine kinase; xenograft nude mouse model This work was supported by funds from the National Program on Key Basic Research Project of China (No 2012CB910704), the Natural Science Foundation of China for Innovation Research Group (No 81021062), the National Natural Science Foundation of China (No 81102461), and the National S&T Major Projects (2012ZX09301001-007). # These three authors contributed equally to this work. * To whom correspondence should be addressed. E-mail mygeng@simm.ac.cn Received 2013-05-17 Accepted 2013-08-02